Belfast Shipbuilders A Titanic Tale - Cameron, Stephen (Blackstaff Press Ltd, 2023)
Belfast once had the largest shipyard in the world, Harland and Wolff. It was there in 1912 that probably the most infamous ship, RMS Titanic, departed from the lough and sailed into the history books. This book traces the growth of the ship building industry in Belfast via stories from the small number of families responsible